STRATEGI GURU DALAM MEMBENTUK KARAKTER DISIPLIN SISWA DI SMAN 1 AIKMEL - Susi Pujianingsih; Mohamad Mustari; Basariah; Yuliatin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to find out the teacher's strategy in shaping the character of student discipline in SMAN 1 Aikmel, which is reviewed from: 1) the teacher's strategy in shaping the character of student discipline in SMAN 1 Aikmel, 2) the supporting and inhibiting factors in shaping the character of student discipline in SMAN 1 Aikmel. The research approach uses a qualitative approach with a descriptive type of research. The research subjects were determined using the Snowball Sampling technique and the data analysis technique using the Miles and Huberman model which consisted of several components, including data collection, data reduction, data presentation and drawing conclusions. The procedure for obtaining data uses observation guidesheets, interview guideline sheets and documentation sheets. Interview and observation sheets are used as a reference to find out how teachers strategies in shaping students disciplinary character. The results of the data acquisition will then be reduced according to the information needed, then the data will be presented and finally the conclusion of the data results that have been analyzed. The results of the research show that 1) teachers strategies in shaping student discipline characters at SMAN 1 Aikmel, namely through learning/designing lesson plans, habituation, example, regulations, punishment and rewards; 2) the driving factors in shaping the character of student discipline, namely from within the student and from the school environment. Meanwhile, the inhibiting factor is from the family environment and the technological factor is the unwise use of cellphones.